IoT Based Smart Saline Bottle for Healthcare - Nivedita Gawade; Rucha Mahalkar; Sakshi More; Snehal Shinde (International Journal of Wireless Security and Networks, 2023)
There is a vast development in the Healthcare sector with the enhancement of Technology. The fundamental principle in caring for hospitalized patients is to ensure that each patient receives high- quality treatment, close monitoring, and appropriate nutrition in a timely manner. Saline is one of the most popular intravenous therapies given to patients in every hospital. Usually in all cases, the patients are normally treated by saline first for dehydration and to help with the patient's health. Continuous monitoring the level of saline is very essential. The patient's saline level is needed to be observed continuously by doctors, nurses or the caretakers. But unfortunately, there are many cases where the health of patients is harmed due to inattentiveness of the hospital staff while observing the completion of the saline bottle. Remote monitoring of saline bottle is required to prevent such situations. Hence automated process for the saline system is very much required for the hospitals.
Keywords: Healthcare; IR sensor; MQTT-S Protocol; NodeMCU; Surveillance; Wi-Fi module